A virulent vasculopathy. (28th March 2011) - Molloy, A; Forde, D; De Gascun, C; Fanning, N; Wyse, G; O'Toole, O
Abstract : Arteriopathy is an uncommon complication of primary varicella zoster virus (VZV) infection in the immunocompetent adult. We report a case of a 39-year-old woman known to be VZV negative prior to the event. She presented to the emergency department having experienced an episode of expressive aphasia and right upper limb paraesthesia lasting 15 min. The symptoms followed a 3-day period of general malaise, arthralgia and a generalised maculopapular itchy rash involving face and limbs. No immunocompromise was detected but an infectious contact was identified in the home. Imaging findings were consistent with a focal cerebritis/vasculopathy and VZV infection was confirmed with cerebrospinal fluid PCR analysis. Resolution of radiological signs occurred following prompt treatment with appropriate antivirals.